Analisis Kredibilitas Konten Informasi Pada Akun Instagram Folkative - Hermawan, Dimas (AGUNA: Jurnal Ilmu Komunikasi, 2025)
The dissemination of information nowadays cannot be separated from the existence of social media. One of the accounts that is quite active in sharing various information content on Instagram is Folkative. Nevertheless, the information content on the Folkative Instagram account has raised specific concerns regarding it’s credibility. The purpose of this research to analyze the credibility of information content on the Folkative Instagram account. The research method uses qualitative with the research approach uses descriptive, through the research data collection techniques uses documentation with the research data analysis techniques uses content analysis. Meanwhile, the research sample consists of the 50 most recent information content posts on the Folkative Instagram account as of 1 May 2025. The research results indicate that the credibility of information content on the Folkative Instagram account can be considered not credible. This is based on the 4 (four) dimensions in the multidimensional information credibility theory proposed by Flanagin & Metzger, namely accuracy dimension, believability dimension, biased dimension, and completeness dimension. Furthermore, the results of this research are expected to urge folkative parties and Instagram users, especially the younger generation to pay more attention to the credibility of information content accessed and shared through virtual networks on social media like Instagram.